A hybrid membrane for all-vanadium redox flow battery and its preparation method

By using a hybrid film with a sulfonated piperazine covalent triazine frame material combined with a sulfonated polymer in an all-vana liquid flow battery, the problems of high vanadium ion permeability and low proton conductivity of the perfluorosulfonic acid film are solved, and a low-cost and high-performance ion conductive film is achieved, which improves the overall efficiency and stability of the battery.

CN116061363BActive Publication Date: 2025-07-18EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310124987.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-16
Publication Date
2025-07-18
Estimated Expiration
2043-02-16

AI Technical Summary

Technical Problem

The existing perfluorosulfonic acid films as ion conductive films of all vanadium flow batteries have problems such as high vanadium ion permeability, low proton conductivity and high cost, and it is necessary to develop low-cost and high-performance ion conductive films.

Method used

The sulfonated piperazine covalent triazine frame material is used to combine with the sulfonated polymer, and hybrid films are prepared by casting method. The nitrogen-rich properties of s-pCTF particles and surface sulfonic acid groups are used to form a donan repulsion and hydrogen bond network, which improves proton conductivity and inhibits vanadium ion penetration.

Benefits of technology

The vanadium resistance and proton conductivity of the hybrid film are significantly improved, the Coulomb efficiency, voltage efficiency and energy efficiency of all vanadium flow batteries are improved, and good chemical stability and battery performance are shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116061363B_ABST
    Figure CN116061363B_ABST
Patent Text Reader

Abstract

The present invention relates to a hybrid membrane for an all-vanadium redox flow battery and a preparation method thereof. In the preparation, a sulfonated piperazine covalent triazine framework material is used as a filler in the mixed membrane and added to a non-fluorosulfonated polymer. Compared with the prior art, the hybrid membrane prepared by the present invention has higher vanadium resistance and proton conduction ability, and exhibits excellent battery performance. The electropositivity exhibited by the particle-rich nitrogen structure enables the macroporous channels to generate Donnan exclusion to achieve high vanadium resistance, while the protonophilic property promotes the construction of a continuous hydrogen bond network in the pores, allowing rapid proton transfer; on the other hand, the sulfonic acid groups grafted on the outer surface of s-pCTF attract and conduct protons, further improving the efficiency of proton conduction through the particles; the synergistic effect of external group attraction-internal channel selective conduction enables s-pCTF particles to be uniformly distributed in the polymer as proton rapid selective transport sites, and the hybrid membrane thereof exhibits good battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of vanadium redox flow batteries, and in particular to a hybrid membrane for all-vanadium flow batteries and a preparation method thereof. Background Art

[0002] Due to environmental protection concepts and the shortage of traditional fossil fuels, the energy demand is gradually shifting towards sustainable green energy, and suitable energy storage technologies still pose a challenge. As a large-scale energy storage technology, the vanadium redox flow battery (VFB) has technical advantages such as high safety, long cycle life, low self-discharge, and adjustable scale, providing an effective way to make full use of renewable energy. As one of the most critical components in the VFB system, the ion-conducting membrane (ICM) serves to isolate the active substances in the anode and cathode while effectively conducting protons to complete the current loop. An ideal ICM needs to meet requirements such as low vanadium ion permeability, high proton conductivity, and excellent chemical durability to ensure efficient energy conversion. Perfluorosulfonic acid membranes (such as Nafion) have excellent proton conductivity and outstanding chemical stability and are currently the most commonly used ICMs, but their relatively high vanadium ion permeability and high manufacturing costs are still problems that need to be urgently solved. Therefore, it is necessary to develop a new generation of low-cost and high-performance ICMs for VFBs.

[0003] Low-cost non-perfluorinated materials are a viable alternative, but they still have drawbacks such as low proton conductivity and poor chemical stability and need to be further modified to obtain high-performance ICMs. Doping functional fillers is a direct and effective strategy to improve the performance of non-perfluorinated membranes. Doping fillers often significantly affect the physical and chemical properties of the membrane. Traditional inorganic fillers (such as TiO2, SiO2, etc.) can increase the vanadium ion permeation resistance by extending the ion transport path, but inevitably result in a decrease in proton conductivity. Porous materials with sub-nanometer pores, such as metal-organic frameworks (MOFs), covalent organic frameworks (COFs), and zeolites, can provide internal intrinsic channels for ion-selective transport and additional proton transfer paths, which is beneficial to breaking the trade-off effect between ion selectivity and proton conductivity in ICMs. Among them, COFs, as a new type of crystalline material, have the advantages of adjustable pore size, highly ordered channels, and customizable functionalization. The organic nature enables COF particles to exhibit good interfacial compatibility with the polymer matrix and is one of the candidates for the next-generation ICM membrane materials. However, the reasonable design and accurate synthesis of COF materials with sub-nanometer pores for pore sieving of vanadium ions and protons remains a challenging problem. Another reason is that the imine bonds (-C=N-) contained in common COFs are in the harsh oxidation environment (H + / VO2 +)It is easy to break in []. As a subtype, covalent triazine framework materials (CTFs) have the excellent general properties of COFs, and their special structure without weak chemical bonds endows them with excellent chemical stability. They are porous materials with potential applications in the ion exchange membranes (ICMs) of all-vanadium redox flow batteries.

[0004] In summary, compared with traditional inorganic fillers, the new functional porous materials have great advantages, but there are also many problems. At present, it is urgent to rationally design processable porous materials with good proton conductivity, high ion selectivity, and chemical stability, which is also an effective strategy for developing high-performance hybrid ICMs. Summary of the Invention

[0005] The purpose of the present invention is to overcome the defects of the above-mentioned existing technologies and provide a hybrid membrane for all-vanadium redox flow batteries and its preparation method. The present invention uses sulfonated polyether ether ketone as the polymer substrate and uniformly disperses functionalized covalent triazine framework materials therein. The functionalized covalent triazine framework material refers to sulfonated piperazine covalent triazine framework material (s-pCTF).

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The first aspect of the present invention provides a preparation method of a hybrid membrane for all-vanadium redox flow batteries, including the following steps:

[0008] Step 1: Prepare a first solution dispersed with sulfonated piperazine covalent triazine framework material;

[0009] Step 2: Prepare a second solution dissolved with sulfonated polymer;

[0010] Step 3: Mix the first solution and the second solution, and then use the casting method to prepare a membrane. After activation, washing, and drying, a hybrid membrane product is obtained.

[0011] Further, both the first solution and the second solution are selected from one or more mixtures of n-butanol, dimethylformamide, dimethyl sulfoxide, isopropyl acetate, and N-methylpyrrolidone.

[0012] Further, the sulfonated piperazine covalent triazine framework material is prepared by the following process:

[0013] (1) Uniformly disperse pCTF particles in hydrogen peroxide solution, stir, filter the product, wash it with water, and vacuum dry to obtain hydroxylated pCTF particles;

[0014] (2) Take the hydroxylated pCTF particles, uniformly disperse them in toluene solution, drop in 3-(trimethoxysilyl)-1-propanethiol (MTPMS), stir, reflux and react, filter the product, wash it with toluene, ethanol, and water several times, and vacuum dry to obtain mercapto-functionalized pCTF particles;

[0015] (3) The thiolated pCTF particles are dispersed in a hydrogen peroxide solution, stirred at room temperature, the filtered product is washed with water, and sulfonated piperazine covalent triazine framework material (s-pCTF) is obtained after vacuum drying.

[0016] Furthermore, the sulfonated piperazine covalent triazine framework material is in the shape of nanoflowers, with a diameter ranging from 300 to 400 nm;

[0017] The doping ratio of the sulfonated piperazine covalent triazine framework material in the sulfonated polymer is 0.1% - 10%.

[0018] More preferably, the doping ratio of the sulfonated piperazine covalent triazine framework material in the sulfonated polymer is 1% - 5%.

[0019] Furthermore, the pCTF particles are prepared by the following process:

[0020] (1) Using tetrahydrofuran as a solvent to dissolve the reaction monomers to obtain a tetrahydrofuran solution of piperazine and a tetrahydrofuran solution of cyanuric chloride respectively;

[0021] (2) Drop N,N - diisopropylethylamine into the piperazine solution, then quickly mix the piperazine solution with the cyanuric chloride solution, react by ultrasonic wave at room temperature, filter and wash with tetrahydrofuran, ethanol and water, and then vacuum dry to obtain white pCTF particles.

[0022] Furthermore, the sulfonated polymer is selected from one of perfluorosulfonic acid, sulfonated polyether ether ketone, sulfonated polyether sulfone or sulfonated polyimide.

[0023] Furthermore, in step three, the activation process is that the hybrid membrane needs to be activated in a sulfuric acid solution with a concentration of 0.1 - 4 mol / L for 24 h.

[0024] Furthermore, by dispersedly introducing the sulfonated piperazine covalent triazine framework material into the sulfonated polymer material, the proton conductivity of the hybrid membrane is improved, the vanadium ion permeation is inhibited, the hydrophilicity is improved, and the coulombic efficiency, voltage efficiency and energy efficiency of the battery are improved.

[0025] Furthermore, the particle size range of the sulfonated piperazine covalent triazine framework material is 300 - 400 nm.

[0026] Furthermore, the proton conduction activation energy of the sulfonated piperazine covalent triazine framework material is 0.117 eV.

[0027] Furthermore, the drying process can use normal pressure and reduced pressure together to thoroughly remove the solvent, and the drying temperature is 60 - 150 °C and the time is 8 - 48 h.

[0028] The second aspect of the present invention provides a hybrid membrane for a vanadium redox flow battery prepared by the above method.

[0029] Further, the thickness of the hybrid membrane for the vanadium redox flow battery is 20 - 60 μm.

[0030] Compared with the prior art, the present invention has the following technical advantages:

[0031] 1) In the present invention, porous sulfonated covalent triazine framework materials are incorporated into sulfonated polymers, significantly improving the physical and chemical properties of the hybrid membrane, including the improvement of vanadium resistance and proton conductivity, and developing a new generation of high-performance ICM for the application of VFB.

[0032] 2) In the present invention, the Donnan exclusion generated by the nitrogen-rich characteristics of pCTF particles allows the internal pores (1.4 - 1.6 nm) of the particles to exhibit a strong hindering effect on vanadium ions, while protons with a smaller diameter and a lower positive charge are subject to a smaller repulsive force. In addition, the tertiary amine groups on the polar pore walls inside pCTF can be protonated under acidic conditions and interact with sulfuric acid to generate N-H + ···HSO4 - interactions to form a continuous hydrogen bond network, which is beneficial to the rapid transport of protons. For s-pCTF, the -SO3H on the outer surface of the particles provides additional proton hopping sites and forms a hydrogen bond network with water molecules, hydrogen ions, sulfate ions, etc., helping protons to enter the internal rapid transport channels. The sulfonic acid groups on the surface enable s-pCTF to effectively improve the proton conduction ability while hindering the penetration of vanadium ions.

[0033] 3) In summary, due to the "outer group attraction - inner channel selective mass transfer" synergistic effect formed by the external sulfonic acid groups of s-pCTF and the internal proton-selective pores, the hybrid membrane exhibits good physical and chemical properties. In the actual VFB battery test, the coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE) have all been significantly improved. Description of the Drawings

[0034] Figure 1 are SEM images of (a) pCTF and (b) s-pCTF powders. (c) and (d) are XRD patterns of pCTF and s-pCTF powders under different chemical conditions.

[0035] Figure 2 are the N2 adsorption - desorption isotherms and pore size distribution curves of (a) pCTF and (b) s-pCTF at 77K.

[0036] Figure 3 are the Arrhenius curves and activation energy values of pCTF and s-pCTF particles.

[0037] Figure 4 Digital photographs of the membranes S / s-pCTF-X (X = 0, 1, 3, 5, 7%).

[0038] Figure 5 Scanning electron microscope images of the S / s-pCTF-X (X = 0, 1, 3, 5, 7%) hybrid membranes, (a) surface view, (b) cross-sectional view, (c) high-magnification cross-sectional view.

[0039] Figure 6 Characterization spectra of XRD and FT-IR of the S / s-pCTF-X (X = 0, 1, 3, 5, 7%) hybrid membranes and s-pCTF particles.

[0040] Figure 7 (a) Water absorption rate and swelling ratio, (b) water contact angle test, (c) ion exchange capacity, (d) proton conduction activation energy curve, (e) thermogravimetric analysis curve of the S / s-pCTF-X (X = 0, 1, 3, 5, 7%) hybrid membranes.

[0041] Figure 8 Performance of the all-vanadium redox flow battery, (a) S / pCTF-X, (b) S / s-pCTF-X (X = 0, 1, 3, 5, 7%), (c) Nafion 212, pure SPEEK membrane, S / s-pCTF-3 membrane, at 40 - 200 mA cm -2 Current density, (d) Long-term cycling performance graphs of the VFB loaded with Nafion212, SPEEK, S / s-pCTF-3 membranes (current density is 120 mAcm -2 ).

[0042] Figure 9 Cross-sectional electron microscope image of S / s-pCTF-3 after completing the long-term cycling test at a current density of 120 mA cm -2 .

[0043] Figure 10 (a) Curves of the vanadium ion permeation amount versus time for SPEEK, S / pCTF-3, and S / s-pCTF-3 membranes, (b) Zeta potential results of pCTF, (c) Free energy curves of V 2+ and H3O + , (d) Curves of the hydrogen ion permeation amount versus time for SPEEK, S / pCTF-3, and S / s-pCTF-3 membranes, (e) Comparison graphs of the selectivity, proton conductivity, and vanadium ion permeability of SPEEK, S / pCTF-3, and S / s-pCTF-3 membranes.

[0044] Figure 11 Schematic diagram of the "synergistic effect" generated by s-pCTF particles. Detailed implementation mode

[0045] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. In the present technical solution, features such as preparation means, materials, structures, or composition ratios that are not clearly described are regarded as common technical features disclosed in the prior art.

[0046] The present invention prepares the required sulfonated piperazine covalent triazine framework particles by a synthesis-post-modification method and adds them to the sulfonated polymer-based membrane material in a certain proportion to prepare an ion exchange membrane with excellent performance. By using the present invention, an ion exchange membrane with high ion selectivity and proton conduction ability can be accurately prepared.

[0047] As Figure 1 shown in Figs. 1a and 1b, both pCTF and s-pCTF are nanoflower-like particles with a particle size distribution in the range of 300 - 400 nm. For the VFB system, the chemical stability of the particles in the hybrid membrane is also crucial. pCTF and s-pCTF have excellent structural stability in solution systems such as water, 3 mol / L sulfuric acid, and oxidative H + / V 5+ and their crystallinity remains good ( Figure 1 Figs. 1c and 1d). The corresponding N2 adsorption-desorption isotherms show that the surface areas of pCTF and s-pCTF do not change significantly, and the pore sizes of both particles are 1.4 - 1.6 nanometers ( Figure 2 ).

[0048] The present invention synthesizes a sulfonated covalent triazine framework material with a sub-2-nanometer pore structure and chemical stability and fills it into a non-fluorosulfonated polymer. Combining the Donnan effect generated by the nitrogen-rich characteristics of the particles and the proton transfer highway formed by the attracting effect of the surface sulfonic acid groups, s-pCTF exhibits excellent vanadium resistance and an extremely low proton conduction activation energy ( Figure 3 ), and its hybrid membrane exhibits good VFB battery performance.

[0049] Examples

[0050] Preparation of piperazine covalent triazine framework (pCTF) and sulfonated piperazine covalent triazine framework (s-pCTF)

[0051] Preparation of pCTF:

[0052] (1) Using 50 mL of tetrahydrofuran as a solvent, 0.8 g of piperazine and 1.1 g of cyanuric chloride were dissolved respectively.

[0053] (2) 3.0 mL of N,N-diisopropylethylamine was dropped into the tetrahydrofuran / piperazine solution, and then the above two solutions were quickly mixed. The reaction was carried out by ultrasonic wave at room temperature (180 W, 40 kHz) for 4 h. After filtration, it was washed several times with tetrahydrofuran, ethanol, and water, and then dried in vacuum at 80 °C for 12 h to obtain white pCTF particles.

[0054] Preparation of s-pCTF:

[0055] (1) Take 0.4 g of pCTF particles and disperse them evenly in 30 mL of hydrogen peroxide solution (30 wt.%). Stir for 4 h. Filter the product and wash it several times with water. After vacuum drying at 80 °C for 12 h, hydroxylated pCTF particles are obtained.

[0056] (2) Take 0.4 g of hydroxylated pCTF particles and disperse them evenly in 30 mL of toluene solution. Drop 3 mL of 3-(trimethoxysilyl)-1-propanethiol (MTPMS) into it, keep the stirring rate at 400 rpm, and reflux at 80 °C for 6 h. Filter the product and wash it several times with toluene, ethanol, and water in sequence. After vacuum drying at 80 °C for 12 h, mercapto-functionalized pCTF particles are obtained.

[0057] (3) Take 0.3 g of mercapto-functionalized pCTF particles and disperse them in 30 mL of hydrogen peroxide solution (30 wt.%). Stir at room temperature for 4 h. Filter the product and wash it several times with water. After vacuum drying at 80 °C for 12 h, sulfonated pCTF particles (s-pCTF) are obtained.

[0058] Preparation of sulfonated polyether ether ketone (SPEEK) and hybrid membranes

[0059] SPEEK is prepared by the sulfonation method. Place the original PEEK 450P powder in an oven at 80 °C for 12 h to completely remove moisture. Add 150 mL of sulfuric acid into a 250 mL three-necked round-bottom flask, start mechanical stirring, preheat the solution to 50 °C, then add 6 g of dry PEEK powder, and keep the temperature and stirring for 5 h. After the reaction is completed, slowly pour the obtained brown homogeneous solution into deionized water to form a shape, and wash it with water many times until the solution is neutral. The prepared SPEEK is dried in an oven at 80 °C.

[0060] Hybrid membranes are prepared by the solution casting method, during which the loading amount of hybrid fillers (0 - 7%) needs to be precisely controlled. The corresponding membranes are denoted as S / A-X, where S is the SPEEK matrix, A is the doped particles (pCTF or s-pCTF), and X is the mass ratio of s-pCTF to SPEEK. The preparation process is as follows: First, add a certain amount of particles into 5.5 mL of N,N-dimethylformamide (DMF) solution, ultrasonically treat for 30 min to preliminarily disperse the particles evenly, and then add 1.5 mL of SPEEK / DMF solution (0.1 g mL -1) Subsequently, ultrasonic treatment was carried out for 3 h and vigorous stirring was carried out for 12 h to form a uniformly dispersed original casting solution. The hybrid membrane was prepared by the solution casting method. After drying in an oven at 80 °C for 6 h, the membrane was placed in a vacuum oven at 100 °C and dried for 12 h to completely remove the solvent. After the membrane was peeled off, it was immersed in a 1 mol / L H2SO4 solution for 24 h for activation, and then washed with an excessive amount of deionized water and stored in water for later use.

[0061] Testing methods

[0062] Swelling and water content

[0063] The swelling ratio (SR) and water uptake (WU) parameters of the membrane respectively reflect the dimensional stability and hydrophilicity of the membrane, and the calculation formulas are as follows:

[0064]

[0065]

[0066] Where L and W are the length and mass of the membrane in the wet and dry states respectively. The membrane was cut into a size of 20×20 mm, taken out after soaking in deionized water for 24 h, the water on the surface was gently blotted with a weighing filter paper, and the length and mass of the sample were quickly measured and recorded. Then the measured membrane sample was placed in an oven at 100 °C and dried for 24 h to completely remove the water, and the length and mass were measured and recorded again. The above steps were repeated three times to obtain the average result.

[0067] Ion exchange capacity

[0068] The ion exchange capacity of the membrane was tested by acid-base titration. Take an activated membrane sample with a mass of about 0.15 g, soak it in a saturated sodium chloride solution for 24 h to completely replace the hydrogen ions in the membrane with sodium ions. Using phenolphthalein as the titration indicator, a 0.1 mol / L sodium hydroxide standard solution was used for titration testing. The calculation formula for the ion exchange capacity of the membrane sample is as follows:

[0069]

[0070] V NaOH is the volume of sodium hydroxide consumed during the titration process (unit: mL); m is the mass of the tested membrane sample in the dry state (unit: g).

[0071] Proton conductivity and activation energy (E a )

[0072] Proton conductivity (σ) (unit: S cm -1 ) data can be tested and calculated using the alternating current impedance method of an electrochemical workstation (model: CHI760E), and the test frequency is 10 -2 -106 Hz, with an AC amplitude of 5 mV. The proton conductivity calculation formula is as follows:

[0073]

[0074] For the hybrid membrane, the in-plane resistance test method of the membrane is adopted. In the above formula, L represents the effective length of the membrane (unit: cm), R is the effective impedance fitted according to the impedance spectrum (unit: Ω), and R represents the cross-sectional area of the membrane (unit: cm 2 ).

[0075] For the particle test, the through-plane resistance test method is adopted. A certain mass of powder is introduced into a special tablet pressing mold with a diameter of 1.2 cm, and the pressure is controlled at 5 Mpa for 10 minutes to obtain the corresponding flaky sample. In the formula, L represents the effective thickness of the particle sheet (unit: cm), R is the effective impedance fitted according to the impedance spectrum (unit: Ω), and R represents the bottom area of the powder sheet (unit: cm 2 ).

[0076] The activation energy (E a ) can be determined by the Arrhenius equation:

[0077]

[0078] Where σ0 is the pre-exponential factor, σ is the proton conductivity at different temperatures, the molar gas constant R = 8.314 J·mol -1 ·K -1 , and T is the absolute temperature (unit: K).

[0079] Vanadium ion permeability and ion selectivity

[0080] The VO 2+ permeability of different membranes is tested through a diffusion cell. The sample membrane with an effective area of 1.767 cm 2 is clamped in the diffusion cell. 50 mL of 1.5 M VOSO4 / 3.0 M H2SO4 solution and 50 mL of 1.5 M MgSO4 / 3.0 M H2SO4 solution are respectively filled on both sides of the diffusion cell, and magnetic stirring is maintained during the test to reduce the concentration polarization on the surface of the sample membrane. Every 12 h, 4 mL of the solution is drawn from the side containing the MgSO4 / H2SO4 solution, and then an equal amount of 1.5 M MgSO4 / 3.0 M H2SO4 solution is added to maintain the osmotic pressure. The concentration change of VO 2+ is detected by a UV-visible spectrophotometer (model: Perkin Elmer Lambda 950), and the concentration of VO 2+ is determined by the standard absorbance / concentration curve. The vanadium ion permeability calculation formula is as follows:

[0081]

[0082] V B is the volume of the MgSO4 / H2SO4 solution, which is 50 mL in this experiment; d(C B (t)) / dt is the change formula of the VO 2+ concentration with respect to time t; C A is the concentration of VO 2+ in the VOSO4 / H2SO4 solution, which is a constant in this experiment; A is the effective area of the sample membrane (cm 2 ); L is the thickness of the membrane (μm); P is the VO 2+ permeability. The ionic selectivity S of the membrane is defined as the ratio of the membrane proton conductivity to the VO 2+ ionic permeability, and the calculation formula is as follows:

[0083]

[0084] Hydrogen ion permeability

[0085] The hydrogen ion permeability was measured using the same diffusion cell. The two sides of the diffusion cell were filled with 50 mL of 1.0 M H2SO4 solution and 50 mL of deionized water, respectively. Magnetic stirring was maintained during the test to reduce the concentration polarization on the surface of the sample membrane. The pH value on the deionized water side was recorded every 30 min, and the hydrogen ion concentration could be obtained by converting the pH curve. The calculation formula for the permeability is as follows:

[0086]

[0087] V B is the volume of the 1.0 M H2SO4 solution, which is 50 mL in this experiment; d(C B (t)) / dt is the change formula of the hydrogen ion concentration with respect to time t; C A is the concentration of hydrogen ions in the deionized aqueous solution, which can be considered a constant in this experiment; A is the effective area of the sample membrane (cm 2 ); L is the thickness of the membrane (μm); P is the hydrogen ion permeability.

[0088] Basic characterization of the membrane

[0089] (1) Figure 4 are the physical pictures of the pure SPEEK membrane and the hybrid membrane. With the increase in the filler content, the color of the hybrid membrane will not change significantly, but the transparency gradually decreases.

[0090] (2) The surface and cross-sectional morphologies of the membrane were investigated using a scanning electron microscope (SEM). As Figure 5As shown, compared with the pure SPEEK membrane, the hybrid membrane loaded with s-pCTF particles presents a rougher surface morphology. The thickness of the hybrid membrane is about 40 μm, and with the increase of the doping amount, a small amount of particle aggregation appears.

[0091] (3) The structure of the membrane was characterized using a Fourier transform infrared spectrometer (FT-IR) and an X-ray diffractometer (XRD). As Figure 6 can be seen, no characteristic peaks of the particles were significantly detected in the hybrid membrane, proving that the particles have good dispersibility.

[0092] (4) The incorporated hydrophilic s-pCTF particles contribute to improving the hydrophilicity and water absorption rate of the hybrid membrane. Its rigid structure and the affinity with the polymer jointly inhibit the swelling of the hybrid membrane ( Figure 7 a, 7b).

[0093] (5) The hybrid membrane exhibits a higher ion exchange capacity under appropriate filler loading, which can be attributed to the protonation of the tertiary amine groups of the particles during the acid activation process. And the ion exchange capacity of the s-pCTF hybrid membrane is higher than that of the pCTF hybrid membrane with the same mass of filler loading, which is due to the influence of the sulfonic acid groups grafted on the outer surface of the s-pCTF particles ( Figure 7 c).

[0094] (6) The s-pCTF particles provide additional proton transport channels, effectively improving the proton conductivity of the hybrid membrane and reducing the activation energy ( Figure 7 d).

[0095] (7) Thermogravimetric analysis (TGA) was performed on the particles and the membrane, and all the membranes showed good thermal stability ( Figure 7 e).

[0096] Single cell performance test of the membrane

[0097] The performance of the membrane was tested using a flow battery system. The system consists of a membrane sample with an effective area of 4.84 cm 2 , two activated carbon felt electrodes, a pair of electrode frames, two conductive graphite plates, several seals and two PTFE housings. The membrane sample is fixed on the electrode frame and clamped between the two electrodes to separate the anolyte (8 mL 1.5 MV 2+ / V 3+ in 3 M H2SO4 solution) and the catholyte (8 mL 1.5 M VO 2+ / VO2 + in 3 M H2SO4). The charge and discharge cut-off voltages for the test are 1.7 V and 0.8 V respectively. The test range of variable current density is 40 - 200 mA cm -2 , with an interval parameter of 20 mA cm -2For the long-term cycling stability test, the current density was controlled to be constant at 120 mA cm -2 during the test. Nitrogen was continuously introduced into the battery to avoid the self-oxidation of vanadium. The Coulombic efficiency (CE), Voltage efficiency (VE), and Energy efficiency (EE) of the battery performance were calculated by the following formulas.

[0098]

[0099]

[0100]

[0101] The hybrid membranes obtained a series of performance results under the same test criteria ( Figure 8 ). Generally speaking, the charge and discharge time of the battery became shorter as the current density increased, resulting in lower vanadium ion permeation and capacity loss, and thus the CE increased with the increase of the current density. However, the larger overpotential and ohmic polarization at high current densities reduced the VE and EE. In terms of specific performance, both the loaded pCTF and s-pCTF particles could significantly improve the battery performance of the hybrid membranes, and the best EE was achieved at 3 wt.% doping. Compared with the S / pCTF-3 membrane, S / s-pCTF-3 showed better battery performance ( Figure 8 a, 8b), indicating that s-pCTF was more suitable for manufacturing advanced ion exchange membranes, which was consistent with the results of the particle activation energy test. This result shows that the rational design of processable porous materials with good proton conductivity, high ion selectivity, and chemical stability is an effective strategy for developing high-performance hybrid ICMs.

[0102] Figure 8 c, 8d integrated the battery performance results of the SPEEK membrane, S / s-pCTF-3 membrane, and commercial Nafion 212 membrane. Due to the inhibitory effect of s-pCTF on vanadium ion permeation, the S / s-pCTF-3 membrane showed excellent CE (97.4% - 98.98%) at all current densities (40 - 200 mA cm -2 ), which was better than the original SPEEK membrane (92.25% - 98.85%) and Nafion 212 (93.3% - 73.72%). At the same time, S / s-pCTF-3 also showed the highest VEs (94.87% - 79.34%) and EEs (92.41% - 78.53%) during the test. At a current density of 120 mA cm -2In the long-term stability test, the S / s-pCTF-3 membrane completed 900 cycles, during which the EE was in the high-performance range (87.2% - 85.0%), which was better than the original SPEEK membrane (740 cycles, EE ≈ 79%), S / pCTF-3 (820 cycles, EE ≈ 81%) and Nafion 212 membrane (530 cycles, EE ≈ 81%). In addition, there was no obvious interfacial gap in the cross-section of S / s-pCTF-3 after the long-term test, reflecting the excellent chemical stability of the hybrid membrane and the good compatibility between the filler and the matrix ( Figure 9 ).

[0103] Vanadium ion permeability and ion selectivity test

[0104] Both S / pCTF-3 and S / s-pCTF-3 showed better vanadium resistance performance than the pure SPEEK membrane. According to the zeta potential test, the pCTF particles showed strong electropositivity. Therefore, it can be considered that the lower vanadium ion permeability of the hybrid membrane is due to the doping of the particles, which is specifically manifested as the Donnan exclusion of vanadium ions by the polar pores of the particles ( Figure 10 a, 10b). To further explore the interaction between vanadium ions and pCTF materials, a DFT-optimized molecular dynamics (MD) model was used to deeply explore the ion permeation process. Among the four valence states of vanadium ions, divalent vanadium ions (V 2+ ) with relatively small diameter and the best diffusion ability were used for the calculation simulation. As Figure 10 c shows, V 2+ needs to overcome a free energy barrier of 11.33 kcal mol -1 to penetrate the pCTF multi-layer structure.

[0105] In addition to the higher vanadium ion permeation resistance, the hybrid membrane also showed more excellent proton conductivity ( Figure 10 d). This can be attributed to the sub-2-nm pores in the doped particles providing sufficient space for the rapid transport of protons. In addition, the tertiary amines on the polar channel walls in the particles can be protonated under acidic conditions and form N-H + ···HSO4 - interactions with sulfuric acid, and the continuous hydrogen bond network formed inside the channel further promotes proton transport. In the same calculation model, the free energy barrier that H3O + needs to overcome to penetrate the pCTF multi-layer structure is only 3.43 kcal mol -1 . This proves that although the pore diameter of the particles is much larger than that of the active ions (pore diameter ≈ 1.5 nm), the pCTF multi-layer can still achieve selective proton conduction through interactions. The theoretical selectivity S calculation formula is as follows:

[0106]

[0107] ΔG is the free energy barrier for ion transport through the structure, and k B is the Boltzmann constant, and T represents the temperature.

[0108] Substituting the relevant parameters, it can be known that the H3O of the pCTF multilayer film + / V 2+ theoretical selectivity is about 6.22×10 5 .

[0109] In addition, for s-pCTF particles, quantum chemical calculations confirmed that the binding energy between the -SO3H groups grafted on the outer surface of the particles and H3O + is 35.03 kJ / mol, which is in the range of ordinary hydrogen bond energies (25 - 40 kJ / mol). This proves that the -SO3H on the outer surface provides additional proton hopping sites, and at the same time forms a hydrogen bond network with water molecules, hydrogen ions, sulfate ions, etc. around the particles, which helps to attract protons into the internal pores for rapid conduction. For the VFB system, the ion selectivity of the membrane (defined as the proton transfer rate and the vanadium ion permeation rate) is related to the vanadium blocking performance and the proton transfer ability. The ion permeation results of the membrane S prove that, compared with pCTF particles, the s-pCTF material can more effectively reduce the proton conduction resistance of the membrane while hindering the permeation of vanadium ions ( Figure 10 e).

[0110] All in all, due to the "outer group attraction - inner channel selective mass transfer" synergistic effect formed by the external sulfonic groups of s-pCTF and the internal proton-selective pores ( Figure 11 ), the S / s-pCTF-3 membrane exhibits good physical and chemical properties and excellent battery performance.

[0111] The above description of the embodiments is for the convenience of those of ordinary skill in the art to understand and use the invention. Obviously, those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative labor. Therefore, the present invention is not limited to the above embodiments, and the improvements and modifications made by those skilled in the art without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A preparation method of a hybrid membrane for a vanadium redox flow battery, characterized in that It includes the following steps: Step 1: Prepare a first solution in which sulfonated piperazine covalent triazine framework material is dispersed; Step 2: Prepare a second solution in which sulfonated polymer is dissolved; Step 3: Mix the first solution and the second solution, and then use the casting method to prepare a membrane. After activation, washing, and drying, a hybrid membrane product is obtained.

2. The preparation method of a hybrid membrane for a vanadium redox flow battery according to claim 1, wherein Both the first solution and the second solution are selected from one or more mixtures of n-butanol, dimethylformamide, dimethyl sulfoxide, isopropyl acetate, and N-methylpyrrolidone.

3. The preparation method of a hybrid membrane for a vanadium redox flow battery according to claim 1, wherein The sulfonated piperazine covalent triazine framework material is prepared by the following process: (1) Uniformly disperse pCTF particles in hydrogen peroxide solution, stir, filter the product, wash it with water, and vacuum dry to obtain hydroxylated pCTF particles; (2) Take the hydroxylated pCTF particles and uniformly disperse them in toluene solution, drop in 3-(trimethoxysilyl)-1-propanethiol (MTPMS), stir, reflux and react, filter the product, wash it several times with toluene, ethanol, and water respectively, and vacuum dry to obtain mercapto-functionalized pCTF particles; (3) Take the mercapto-functionalized pCTF particles and disperse them in hydrogen peroxide solution, stir at room temperature, filter the product, wash it with water, and vacuum dry to obtain sulfonated piperazine covalent triazine framework material (s-pCTF).

4. The preparation method of a hybrid membrane for an all-vanadium redox flow battery according to claim 1, characterized in that, The sulfonated piperazine covalent triazine framework material is in the shape of nanoflowers, and the diameter range is 300 - 400 nm; The doping ratio of the sulfonated piperazine covalent triazine framework material in the sulfonated polymer is 0.1% - 10%.

5. The preparation method of a hybrid membrane for a vanadium redox flow battery according to claim 3, characterized in that, The pCTF particles are prepared by the following process: (1) Use tetrahydrofuran as a solvent to dissolve the required solutes to obtain a tetrahydrofuran solution of piperazine and a tetrahydrofuran solution of cyanuric chloride respectively; (2) Drop N,N-diisopropylethylamine into the piperazine solution, then quickly mix the piperazine solution with the cyanuric chloride solution, react by ultrasonic wave at room temperature, filter, wash with tetrahydrofuran, ethanol, and water, and then vacuum dry to obtain white pCTF particles.

6. The preparation method of a hybrid membrane for a vanadium redox flow battery according to claim 1, characterized in that The sulfonated polymer is selected from one of perfluorosulfonic acid, sulfonated poly(ether ether ketone), sulfonated poly(ether sulfone), or sulfonated polyimide.

7. The preparation method of a hybrid membrane for a vanadium redox flow battery according to claim 1, characterized in that, In Step 3, the activation process is to activate the hybrid membrane in a sulfuric acid solution with a concentration of 0.1 - 4 mol / L for 24 h.

8. The preparation method of a hybrid membrane for a vanadium redox flow battery according to claim 1, characterized in that, By dispersively introducing the sulfonated piperazine covalent triazine framework material into the sulfonated polymer, the proton conductivity, hydrophilicity of the hybrid membrane are improved, the vanadium ion permeation is inhibited, and the coulombic efficiency, voltage efficiency, and energy efficiency of the battery are increased.

9. A hybrid membrane for an all-vanadium redox flow battery prepared by the method according to any one of claims 1 to 8.

10. A hybrid membrane for a vanadium redox flow battery according to claim 9, characterized in that, The thickness of the hybrid membrane for the all-vanadium redox flow battery is 20 - 60 μm.